Orogastric tube placement during trauma arrest - Russell A. Baker; Sunny Baker (Journal of the American College of Emergency Physicians Open, 2020)
Abstract Misdirection of nasogastric tubes into the cranial cavity of trauma patients is a well‐understood complication that has been well documented in the literature. As a result, recommendations have been established in the use of nasogastric tubes where trauma or suspected skull fractures are identified. Orogastric tube placement is also a commonly performed procedure during trauma resuscitation attempts and is often necessary during patient management. However, no literature currently exists demonstrating misdirection of orogastric tube placement into the spinal canal following trauma and as such, no similar recommendations exist. We review a case of orogastric tube misplacement into the spinal canal due to atlanto‐occipital dissociation and suggest a recommendation for prevention.